2018
DOI: 10.3389/fmicb.2018.02296
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ozonated Water, Chlorine, Chlorine Dioxide, Quaternary Ammonium Compounds and Peroxyacetic Acid Against Listeria monocytogenes Biofilm on Polystyrene Surfaces

Abstract: Listeria monocytogenes contaminated processing equipment and the general packing environment have been implicated in deadly foodborne listeriosis outbreaks, highlighting the significance of proper sanitization and disinfection of food contact surfaces. This study aims to comprehensively evaluate antimicrobial efficacy of commercially available, economical sanitizers at practical concentrations against L. monocytogenes biofilm formed on polystyrene surfaces under different conditions. Ozonated water 1-min treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 38 publications
5
17
0
1
Order By: Relevance
“…QAC sanitizers are often used in food processing facilities and have also been applied in facility X, which was the source of the 40 isolates studied here. The cationic, cell membrane-acting sanitizer is usually applied at concentrations of 200 to 400 ppm and has been shown to effectively reduce L. monocytogenes (more than a 3-log reduction) (29)(30)(31)(32). However, traces of highly diluted sanitizer can reach niches harboring L. monocytogenes, and isolates carrying the QAC tolerance genes might have a growth advantage at low-level sanitizer concentrations (32).…”
Section: Discussionmentioning
confidence: 99%
“…QAC sanitizers are often used in food processing facilities and have also been applied in facility X, which was the source of the 40 isolates studied here. The cationic, cell membrane-acting sanitizer is usually applied at concentrations of 200 to 400 ppm and has been shown to effectively reduce L. monocytogenes (more than a 3-log reduction) (29)(30)(31)(32). However, traces of highly diluted sanitizer can reach niches harboring L. monocytogenes, and isolates carrying the QAC tolerance genes might have a growth advantage at low-level sanitizer concentrations (32).…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that S. aureus was the most sensitive species for ozone dissolved in water [27]. Korany et al [28] showed that the use of ozonated water (1 min) against the structure of L. monocytogenes biofilm on the surface of polystyrene at the concentration of 1.0, 2.0, and 4.0 ppm resulted in a bacterial number reduction of 0.9, 3.4, and 4.1 log CFU/cm 2 , respectively. Moreover Korany et al [28] found that quaternary ammonium compounds (QAC) (100/400 ppm), chlorine (100/200 ppm), chlorine dioxide (2.5/5.0 ppm) and peracetic acid (PAA) (80/160 ppm) resulted in a reduction of 2.4/3.6, 2.0/3.1, 2.4/3.8, and 3.6/4.8 log CFU/cm 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Korany et al [28] showed that the use of ozonated water (1 min) against the structure of L. monocytogenes biofilm on the surface of polystyrene at the concentration of 1.0, 2.0, and 4.0 ppm resulted in a bacterial number reduction of 0.9, 3.4, and 4.1 log CFU/cm 2 , respectively. Moreover Korany et al [28] found that quaternary ammonium compounds (QAC) (100/400 ppm), chlorine (100/200 ppm), chlorine dioxide (2.5/5.0 ppm) and peracetic acid (PAA) (80/160 ppm) resulted in a reduction of 2.4/3.6, 2.0/3.1, 2.4/3.8, and 3.6/4.8 log CFU/cm 2 , respectively. The antimicrobial efficacy of all tested disinfectants against the 7-day L. monocytogenes biofilm was significantly lower compared to 2-day biofilms, and the biofilm age having the minor impact on the effectiveness of PAA [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations